Marta Erdman’s “Hyphenated People”. A Contribution to Nonlinear Biography - Brzezińska, Anna (Sensus Historiae, 2021)
The paper is dedicated to Marta Erdman, the younger daughter of Melchior Wańkowicz. I propose to discuss her own experience of Polishness, which she faced in her essays published in Jerzy Giedroyc’s “Kultura.” The subject of analysis is Erdman’s search for her own identity in confrontation with the family patriotic tradition, the experiences from the Second World War and emigration, and with the legend of her father.